CURRENT BENCHMARKS ON THE NATIONAL RECOVERY AND RESILIENCE PLAN, AN INSTRUMENT THAT PROMOTES FINANCING FOR RESULTS ‒ DIRECT FINANCIAL SUPPORT FOR THE MINISTRY OF NATIONAL DEFENCE - Carmen-Gabriela NIȚU (CHITAFES) (Bulletin of "Carol I" National Defense University, 2021)
This article will discuss in detail the role of the National Recovery and Resilience Plan (NPRR), a topic that deserves attention, because it is a budget support for reform, a new mechanism that has been thought on a totally different logic, correlated with the approach used for the management of cohesion funds and will also highlight the fact that the Ministry of National Defence was introduced among the institutions involved in updating this plan. At the level of the Romanian state, ”the Ministry of European Investments and Projects was mandated to coordinate and be responsible for the process of elaboration and negotiation of NPRR with the European Commission”. The Ministry of National Defence has the quality of institution involved in the following fields of intervention: Transport, Health, Education, Research, innovation, digitalization as well as Resilience in crisis situations. Through the Recovery and Resilience Mechanism (RRF), the European Union (EU) provides funded Member States for the implementation of systemic and structural reforms and investigations, harmonized with EU priorities and policies.